Investigation of the Elemental Analysis of Carbonaceous Kenaf Fiber from HTC Process - Norlirabiatuladawiyah, Che Ani; Saidatul Shima, Jamari; Khan, Tanveer Ahmed (2015)
This paper presents a preliminary investigation on producing carbonaceous product from Kenaf fiber using Hydrothermal Carbonization process also known as HTC. The process was conducted at different pre-treatment time of 2h, 4h, 6h, 8h and 10h at temperature of 225°C. This work aimed to identify the level of optimization of biomass dry weight for the carbonization of Kenaf fiber. The results indicated that HTC has the ability to convert biomass to biochar with high carbon content and lower O/C and H/C ratios. In addition, the lowest carbon content at 4h due to hydrolysis reaction while others operating time enhanced dehydration reaction due to higher carbon produced. In future, the longer operating time will be conducted to determine the optimization percentage of biochar.